The Value, Realistic Challenges, and Practical Paths of Carrying out National Defense Education in Vocational College Student Apartments - Luo, Zhaomao; Liu, Hong; Xu, Hongjun; Mou, Yurui (Journal of Educational Research and Policies, 2024)
Under the guidance of strengthening national defense education for all, the national defense education work of ordinary vocational colleges has entered the fast lane, and has achieved remarkable results and achievements in regulations, theoretical teaching, skill training, scientific research achievements, and teacher team construction. In order to further strengthen national defense education in universities, continuously expand the carrier platform and methods of national defense education, this paper analyzes the significance, current situation and shortcomings of carrying out national defense education in vocational college student apartments, and proposes targeted ways and methods to carry out national defense education, providing ideas and references for effectively improving national defense education in vocational colleges.